Grover$1 (Bs bad, awful day s - Dickson, Anna H.; Brannon, Tom; Children$1 (Bs Television Workshop.s ([New York] : Western Pub. Co. in conjunction with Children$1 (Bs Television Workshop,s, 1986)
Mommy comforts Grover after he has a bad, awful day.
"Featuring Jim Henson$1 (Bs Sesame Street Muppets."s
"A Sesame Street/Golden Press book."
"A Golden book"--Cover.
Keywords: Puppets -- Fiction